Coverage of antenatal iron-folic acid and calcium distribution during pregnancy and their contextual determinants in the northeastern region of India - Bora, Kaustubh; Barman, Bhupen; Pala, Star; Das, Ananya; Doke, Goter; Tripura, Amar (Frontiers in Nutrition, 2022)
Iron-folic acid (IFA) and calcium supplementation are nutritional interventions recommended prophylactically (against maternal anemia and preeclampsia, respectively) to all antenatal mothers in India under basic antenatal care (ANC) services. Using Health Management Information System data (reporting period: 2018–19 to 2020–21), we mapped the coverage of antenatal IFA and calcium distribution across the remote northeastern region of India relative to the number of pregnant women (PW) who registered for ANC, disaggregated by states and districts. Variations in coverage were also investigated by subgroups based on contextual attributes, viz., physiography (mountain/ plateau/ plain), socioeconomic condition (‘aspirant’/ ‘non-aspirant’) and proportion of early ANC visits (low/ medium/ high). Full course of antenatal IFA and calcium supplements were received by 79.36 (95% CI: 79.31–79.40) and 61.26 (95% CI: 61.21–61.32) PW per 100 ANC registered women, respectively. There were widespread heterogeneity in outreach, with calcium coverage generally trailing behind IFA coverage. Among states, coverage of the two interventions (per 100 ANC registered women) was highest in Assam (97.06 and 78.11 PW, respectively) and lowest in Nagaland (24.87 and 16.77 PW, respectively). At the district-level, the two interventions failed to reach even 50 PW per 100 ANC registered women in 32 (out of 115) districts. The coverage tended to be inferior in districts that were mountainous, ‘non-aspirant’ and had low proportion of early ANC visits. The granular information provided by our findings will facilitate monitoring, root cause analyses, microplanning, informed resource allocation and tailoring of locally appropriate solutions to achieve targeted coverage improvements.